Metamorphoses of Slovenian folk dance - Ramovš, Mirko (Traditiones (Ljubljana), 2005)
Similar to other phenomena in folk culture, folk dance has been subject to different influences throughout its existence that changed its form, strukcture, style, and function in people's everyday and festive lives. This paper analyses the changes that have taken place and tries to categorize them and establish reasons for them. The paper is primarily based on dance recorded after World War II, in combination with materials collected in the program of the Committee for the Collection of Slovenian Folks Songs at the beginning of the 20th century
Keywords: slovenski ljudski plesi; metamorfoze; zgodovinski pregledi; Slovenia; Slovenija